(3ZGjI GdShd aj SjQI GdQShds - (3YHO GdHGSW Hf Ndjd Hf TGgjf GdedWj, Ke GdbGgQj, Rjf GdOjf,J (B920 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi HYK QShdg eMeOkG Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3gPG BNQ eGbUOfGg ef HjGf SjQI fHjfG eMeO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B270 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B68s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B52 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B192 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs